ADOPSI ANAK OLEH KOMUNITAS LGBTQ+ DALAM PERSPEKTIF HUKUM KELUARGA ISLAM TELAAH KOMPARATIF FIQH KLASIK DAN PENDEKATAN HUMANIS KONTEMPORER - Ahmad ahmad; Agus Muchsin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines child fostering (tabanni) by the LGBTQ+ community from the perspective of Islamic family law through a comparative analysis of classical fiqh and contemporary humanistic approaches. Its objective is to formulate an inclusive tabanni framework that balances Sharia principles with modern social dynamics in Indonesia. Employing a qualitative normative-empirical design, the research integrates textual analysis of classical fiqh documents from the four major Sunni schools (Hanafi, Maliki, Shafi'i, Hanbali)-such as Al-Mughni, Bidayat al-Mujtahid, and Fath al-Qarib-with semi-structured interviews and focus group discussions involving 8-15 progressive Muslim respondents in Jakarta and Yogyakarta (2023-2025). Classical fiqh emphasizes child welfare without altering nasab status, within a heteronormative framework that prohibits full inheritance or mahram rights. In contrast, the contemporary humanistic approach, advocated by progressive Muslims, reinterprets tabanni through maqasid al-shariah (hifz al-nas and hifz al-ird), prioritizing verified caregiver suitability, transparent mechanisms, and cross-community dialogue. The integration of these approaches yields an inclusive tabanni framework encompassing caregiver verification criteria, preservation of the child's nasab, Sharia-based formal processes, and educational programs to address conservative resistance. These findings enhance child protection while offering contextual recommendations for more equitable and responsive Islamic family law in Indonesia's pluralistic society.